Solid electrolyte and application thereof

By covering the shell containing lithium iodide and lithium fluoride on the surface of the core body of the solid electrolyte, the problem of poor stability of sulfide electrolyte to air and positive and negative electrodes is solved, and the cycle life and stability of all solid state batteries are improved.

CN119627194AActive Publication Date: 2025-03-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1

Patent Information

Application Number
CN202411824668.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In practical applications, the sulfide electrolyte has poor stability to air and positive and negative electrodes, which affects the cycle life and stability of all-solid-state batteries.

Method used

By covering the shell layer on the surface of the core body of the solid electrolyte, the shell layer includes lithium iodide and lithium fluoride, preventing electron transport, preventing interface reactions, and improving ion transport capabilities.

Benefits of technology

Improves the stability of solid electrolytes to air and positive and negative electrodes, improves the cycle life and stability of all-solid state batteries, and enhances electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627194A_ABST
    Figure CN119627194A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte and application thereof, and the solid electrolyte at least comprises: a core body comprising a sulfide electrolyte; the surface of the core body is coated with the shell layer, and the shell layer comprises lithium iodide and lithium fluoride. According to the solid electrolyte and the application thereof provided by the invention, the stability of the solid electrolyte to air and positive and negative electrodes can be improved, so that the cycle life and the stability of a battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and particularly to a solid electrolyte and its application. Background Art

[0002] Sulfide electrolytes have advantages such as high ionic conductivity, wide electrochemical window, and good mechanical properties. They are considered to be one of the most commercially promising solid electrolytes and are thus widely used in all-solid-state batteries. However, in practical applications, sulfide electrolytes have poor stability against air and the positive and negative electrodes, which affects the performance of all-solid-state batteries such as cycle life and stability, severely restricting the further development and application of the batteries. Summary of the Invention

[0003] The present invention provides a solid electrolyte and its application. By using the solid electrolyte and its application provided by the present invention, the stability of the solid electrolyte against air and the positive and negative electrodes can be improved, thereby enhancing the cycle life and stability of the battery.

[0004] To solve the above technical problems, the present invention provides a solid electrolyte, which at least includes:

[0005] A core, including a sulfide electrolyte; and

[0006] A shell layer, covering the surface of the core, and the shell layer includes lithium iodide and lithium fluoride.

[0007] In an embodiment of the present invention, the chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, and X is selected from at least one of Cl, Br, or I.

[0008] In an embodiment of the present invention, M is selected from at least one of Sb, In, or Bi, X is Cl, and the value range of b is 0 < b ≤ 0.1.

[0009] In an embodiment of the present invention, the chemical formula of the sulfide electrolyte is Li f P 1-g E g S w O g Q z, where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.

[0010] In an embodiment of the present invention, E is Mg, Q is Cl, and the value range of g is 0.01 ≤ g ≤ 0.1.

[0011] In an embodiment of the present invention, in the shell layer, the mass ratio of lithium iodide to lithium fluoride is (1 - 10):1.

[0012] In an embodiment of the present invention, the thickness of the shell layer is 1 nm to 100 nm.

[0013] In an embodiment of the present invention, after the solid electrolyte is exposed to humid air with a dew point temperature of -40° for 24 h, the retention rate of the ionic conductivity is 55% - 96%.

[0014] The present invention also provides a all-solid-state battery, at least including:

[0015] a positive electrode plate;

[0016] a negative electrode plate; and

[0017] a solid electrolyte membrane, disposed between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane includes the above-mentioned solid electrolyte.

[0018] The present invention also provides an electronic device, including the above-mentioned all-solid-state battery.

[0019] In summary, the present invention proposes a solid electrolyte and its application. By improving the solid electrolyte in the all-solid-state battery and coating a shell layer on the surface of the core body, it can effectively prevent electrons from being transmitted between the core body and the positive and negative electrode materials, avoid interfacial reactions between the core body and the positive and negative electrode materials, improve the stability of the solid electrolyte to the positive and negative electrodes, and thus improve the cycle life and stability of the all-solid-state battery. The shell layer can also prevent the core body from directly contacting with moisture and oxygen in the air, avoid reactions between the core body and moisture and oxygen in the air, improve the stability of the solid electrolyte to air, and thus further improve the cycle life of the battery. Moreover, lithium iodide in the shell layer can effectively improve the ion transport ability of the solid electrolyte, enhance the electrochemical performance of the solid electrolyte, while improving the wettability between the solid electrolyte and the positive and negative electrode materials, promoting ion transport at the interface between the solid electrolyte and the positive and negative electrode materials, and improving the stability of the interface. Description of the Drawings

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0021] Figure 1 This is a graph showing the results of a room temperature cycle performance test on the all-solid-state battery in Example 3 of the present invention. DETAILED DESCRIPTION

[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0023] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0024] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] The present invention provides a solid electrolyte, for example, including a core and a shell, etc. Wherein, the core includes a sulfide electrolyte, the shell is coated on the surface of the core, and the shell includes lithium iodide and lithium fluoride. In the solid electrolyte provided by the present invention, by setting the shell, it is possible to effectively prevent electrons from being transmitted between the core and the positive and negative electrode materials, avoid interfacial reactions between the core and the positive and negative electrode materials, improve the stability of the solid electrolyte to the positive and negative electrodes, thereby improving the cycle life and stability of the all-solid-state battery. Moreover, the shell can prevent the core from directly contacting the moisture and oxygen in the air, avoid the reaction of the core with the moisture and oxygen in the air, improve the stability of the solid electrolyte to the air, thereby further improving the cycle life of the battery.

[0026] In one embodiment of the present invention, in the core, the sulfide electrolyte can improve the interface stability between the solid electrolyte and the negative electrode, ensure a continuous and stable lithium ion transmission channel, reduce the interface impedance, and improve the charge transfer efficiency. Specifically, the chemical formula of the sulfide electrolyte is selected from Lia P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z at least one of etc. Among them, in Li a P 1-b M b S c O d X e wherein, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, etc. X is selected from at least one of Cl, Br, or I, etc. Further, M is, for example, selected from at least one of Sb, In, or Bi, X is Cl, and the value range of b is, for example, 0 < b ≤ 0.1. More specifically, when M is, for example, a +5 valence element, b is, for example, 0.04, and when M is, for example, a +3 valence element, b is, for example, 0.02. By controlling the types of M and X elements and the value range of b in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be improved, thereby extending the service life of the battery.

[0027] In one embodiment of the present invention, when the chemical formula of the sulfide electrolyte is Li f P 1-g E g S w O g Q z wherein, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, or Pb, etc. Q is selected from at least one of Cl, Br, or I, etc. Further, E is, for example, Mg, Q is, for example, Cl, and the value range of g is, for example, 0.01 ≤ g ≤ 0.1. Specifically, g is, for example, 0.02. By controlling the type of E element, the type of Q element, and the value range of g in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be improved, thereby extending the service life of the battery.

[0028] In one embodiment of the present invention, in the shell layer, lithium iodide has a high ionic conductivity, which can effectively improve the ion transmission capacity of the solid electrolyte and enhance the electrochemical properties of the solid electrolyte. Moreover, it can improve the wettability between the solid electrolyte and the positive and negative electrode materials, promote the transmission of ions at the interface between the solid electrolyte and the positive and negative electrode materials, and improve the stability of the interface.

[0029] In one embodiment of the present invention, in the shell layer, lithium fluoride has extremely low electronic conductivity, high chemical inertness and high interface energy, and can form a stable protective layer on the surface of the core body. On the one hand, it can effectively prevent electrons from being transmitted between the core body and the positive and negative electrode materials, avoid interfacial reactions between the core body and the positive and negative electrode materials, improve the stability of the solid electrolyte to the positive and negative electrodes, and thus improve the cycle life and stability of the all-solid-state battery. On the other hand, it can prevent the core body from directly contacting with moisture and oxygen in the air, avoid the reaction of the core body with moisture and oxygen in the air, improve the stability of the solid electrolyte to air, and further improve the cycle life of the battery.

[0030] In one embodiment of the present invention, in the shell layer, the mass ratio of lithium iodide to lithium fluoride is, for example, (1-10): 1. Lithium fluoride has good chemical stability but poor electrical conductivity. By controlling the mass ratio of lithium iodide to lithium fluoride in the shell layer, the stability of the solid electrolyte to air can be improved, while avoiding the problem of reduced electrical conductivity of the solid electrolyte caused by excessive lithium fluoride content, thereby improving the cycle performance of the battery.

[0031] In one embodiment of the present invention, the thickness of the shell layer is, for example, 1 nm to 100 nm, and the ion conductivity retention rate of the solid electrolyte after being exposed to moist air at a dew point temperature of -40° for 24 hours is, for example, 55% to 96%. By controlling the thickness of the shell layer, the stability of the solid electrolyte to air and the positive and negative electrodes can be improved, and the problem of reduced conductivity of the solid electrolyte caused by excessive thickness of the shell layer can be avoided, thereby improving the cycle performance of the battery.

[0032] In one embodiment of the present invention, when preparing the solid electrolyte, first, in an atmosphere of an inert gas such as argon, according to the chemical formula of the sulfide electrolyte Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z, after the Li source, P source, M source, S source and X source, or the Li source, P source, E source, S source and Q source are uniformly mixed according to the stoichiometric ratio, for example, they are placed in a ball mill for ball milling to obtain a precursor powder, and then the precursor powder is subjected to high temperature annealing and sintering to obtain a core material. Wherein, the Li source is selected from at least one of Li2S, LiCl, LiBr or lithium iodide, the P source is P2S5, the M source is an oxide of M, the S source is from at least one of the Li source or P source, the X source is from the Li source, the E source is an oxide of E, the Q source is from the Li source, the ball-to-material mass ratio is (1-100):1, the ball milling time is 1h-48h, the rotation speed is 50rpm-1500rpm, the sintering temperature is 400℃-600℃, and the sintering time is 1h-48h.

[0033] In one embodiment of the present invention, after obtaining the core body, the core body, the fluorine-containing compound and the iodine-containing compound are mixed evenly, for example, placed in a sealed quartz bottle or polytetrafluoroethylene bottle for heat treatment, the iodine-containing compound and the fluorine-containing compound react with the lithium in the core body to generate lithium iodide and lithium fluoride coated on the surface of the core body, and a solid electrolyte is obtained after cooling. Wherein, the fluorine-containing compound is selected from at least one of lithium hexafluorophosphate, ammonium hydrogen fluoride or ammonium fluoride, etc., the iodine-containing compound is selected from at least one of I2 or ammonium iodide, etc., the mass ratio of the fluorine-containing compound to the core body is, for example, 1: (1 to 100), the mass ratio of the iodine-containing compound to the core body is, for example, 1: (1 to 100), the temperature of the heat treatment is, for example, 30°C to 250°C, and the time of the heat treatment is, for example, 1h-24h. In this embodiment, the core body, the fluorine-containing compound and the iodine-containing compound are mixed and heat treated, and a shell structure can be quickly constructed on the surface of the core body, thereby improving the preparation efficiency of the solid electrolyte, and simplifying the preparation method of the solid electrolyte and reducing the preparation cost.

[0034] The present invention also provides an all-solid-state battery, for example, including a positive electrode plate, a negative electrode plate and a solid electrolyte membrane. The solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane is obtained by cold pressing the above-mentioned solid electrolyte under a pressure of 300MPa to 400MPa, and the thickness of the solid electrolyte membrane is, for example, 100μm to 500μm. In the present invention, the all-solid-state battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the types and types of the all-solid-state battery.

[0035] In one embodiment of the present invention, the positive electrode plate includes, for example, a positive electrode active layer, and the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a conductive agent, and a binder. Among them, the present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the conductive agent, and the binder, which can be selected according to actual needs. In other embodiments of the present invention, in addition to the positive electrode active layer, the positive electrode plate may also include a positive electrode collector, and the positive electrode collector is coated with a positive electrode active layer on the surface of at least one side. Among them, the positive electrode collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.

[0036] In one embodiment of the present invention, in the positive electrode active layer, the positive electrode active material is selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA), the positive electrode electrolyte is a halide solid electrolyte, the conductive agent is selected from at least one of graphite, graphene, conductive carbon black (SuperP), nanocarbon fiber (vapor-grown carbon fiber, VGCF) or carbon nanotubes, and the binder is selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAN), etc. At least one of polyol, polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, fluorine rubber, β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer.

[0037] In one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is for example Li 2.35 Zr0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1, and the binder is, for example, PTFE. After the positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are uniformly mixed in a mass ratio of, for example, 69:29:1:1, the positive electrode sheet is directly obtained by dry pressing.

[0038] In another embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is for example Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1, and the binder is, for example, PTFE. The positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are mixed evenly in a mass ratio of, for example, 69:29:1:1, and then rolled and covered on the surface of the aluminum foil to obtain a positive electrode sheet.

[0039] In one embodiment of the present invention, the negative electrode plate is selected from at least one of a metal lithium plate, a metal indium plate or a lithium indium alloy plate. In other embodiments of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector. Among them, the negative electrode current collector is, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector or a stainless steel current collector, and the negative electrode active layer includes, for example, a negative electrode active material, a negative electrode electrolyte, a conductive agent and a binder. The present invention does not limit the mass ratio of the negative electrode active material, the negative electrode electrolyte, the conductive agent and the binder, and can be selected according to actual needs.

[0040] In one embodiment of the present invention, the negative electrode active material is selected from at least one of graphite materials or silicon materials, the negative electrode electrolyte is, for example, a sulfide solid electrolyte, the conductive agent is selected from at least one of graphite, graphene, SuperP, VGCF or carbon nanotubes, and the adhesive is selected from at least one of PVDF, CMC, SBR, PVP, PMMA, PAN, PAA, polyurethane, PVA, Alg, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-CDp, LA132, PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer.

[0041] In one embodiment of the present invention, the negative electrode current collector is, for example, a copper foil current collector, the negative electrode active material is, for example, silicon, the negative electrode electrolyte is, for example, a sulfide solid electrolyte, the conductive agent is, for example, SuperP, and the binder is, for example, PTFE. The negative electrode active material, the negative electrode electrolyte, the conductive agent, and the binder are mixed evenly in a mass ratio of, for example, 72:20:5:3, and then rolled and covered on the surface of the copper foil current collector to obtain a negative electrode sheet.

[0042] In one embodiment of the present invention, the above-mentioned positive electrode sheet, solid electrolyte membrane and negative electrode sheet are sequentially stacked, packaged, hot pressed and cold pressed to assemble into an all-solid-state battery. The assembly process of the all-solid-state battery is completed in an inert atmosphere glove box.

[0043] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0044] Example 1

[0045] Preparation of the core: Under an argon atmosphere, 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 were added to a ball mill for high-energy ball milling to obtain a precursor powder, wherein the ball-to-material ratio was 30:1, the rotation speed was 500 rpm, and the ball milling time was 20 h. After the ball milling, the precursor powder was sintered at 500 ° C for 10 h to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide electrolytes.

[0046] Preparation of solid electrolyte: Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 After the sulfide electrolyte, ammonium bifluoride and I2 are mixed evenly, they are poured into a sealed polytetrafluoroethylene bottle, and then heat treated at 250°C for 6 hours, and a solid electrolyte is obtained after cooling. Among them, the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:1:1.

[0047] Preparation of solid electrolyte membrane: The solid electrolyte was cold pressed at 350 MPa to obtain a 300 μm solid electrolyte membrane.

[0048] Preparation of positive electrode: LiNi 0.8 Co0.1 Mn 0.1 O2 positive electrode active material, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The positive electrode electrolyte, the conductive agent and PTFE are mixed evenly in a mass ratio of 69:29:1:1, for example, and then the positive electrode sheet is obtained by dry pressing and cut into discs with a diameter of 10 mm. The conductive agent includes SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1.

[0049] Choice of negative electrode: Choose metallic lithium as the negative electrode.

[0050] Battery preparation: The positive electrode sheet, solid electrolyte membrane and negative electrode sheet are stacked, packaged, hot pressed and cold pressed in sequence to assemble into an all-solid-state battery.

[0051] Example 2

[0052] The difference between this embodiment and embodiment 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:2:2.

[0053] Example 3

[0054] The difference between this embodiment and embodiment 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:3:3.

[0055] Example 4

[0056] The difference between this embodiment and embodiment 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:10:10.

[0057] Example 5

[0058] The difference between this embodiment and embodiment 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:20:20.

[0059] Example 6

[0060] The difference between this embodiment and embodiment 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:1:5.

[0061] Example 7

[0062] The difference between this embodiment and embodiment 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:2:4.

[0063] Example 8

[0064] The difference between this embodiment and embodiment 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:4:2.

[0065] Example 9

[0066] The difference between this embodiment and embodiment 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:5:1.

[0067] Example 10

[0068] The difference between this embodiment and embodiment 3 is that the fluorine-containing compound in the preparation process of the solid electrolyte is ammonium fluoride, and the mass ratio of the sulfide electrolyte, ammonium fluoride and I2 is 100:3:3.

[0069] Embodiment 11

[0070] The difference between this embodiment and embodiment 3 is that the iodine-containing compound in the solid electrolyte preparation process is ammonium iodide, and the mass ratio of the sulfide electrolyte, ammonium bifluoride and ammonium iodide is 100:3:3.

[0071] Example 12

[0072] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.99 Sb 0.0 1S 4.475 O 0.025 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.05 mol of Sb2O5.

[0073] Embodiment 13

[0074] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Sb2O5.

[0075] Embodiment 14

[0076] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.9 Sb 0.1 S 4.25 O0.25 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Sb2O5.

[0077] Embodiment 15

[0078] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.96 Sb 0.0 4S 4.40 O 0.10 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of lithium iodide, 0.48 mol of P2S5 and 0.02 mol of Sb2O5.

[0079] Example 16

[0080] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.52 P 0.99 In 0.0 1S 4.485 O 0.015 Cl 1.5 The raw materials are 2.01 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of In2O3.

[0081] Embodiment 17

[0082] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 In 0.0 2S 4.47 O 0.03 Cl 1.5 The raw materials are 2.02 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of In2O3.

[0083] Embodiment 18

[0084] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.62 P 0.94 In 0.0 6S 4.41 O 0.09 Cl 1.5The raw materials are 2.06 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of In2O3.

[0085] Embodiment 19

[0086] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 The raw materials are 2.1 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of In2O3.

[0087] Embodiment 20

[0088] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 In 0.0 2S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.02 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of lithium iodide, 0.49 mol of P2S5 and 0.01 mol of In2O3.

[0089] Embodiment 21

[0090] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.52 P 0.99 Bi 0.0 1S 4.485 O 0.015 Cl 1.5 The raw materials are 2.01 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Bi2O3.

[0091] Embodiment 22

[0092] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 Bi 0.0 2S 4.47 O 0.03 Cl 1.5The raw materials are 2.02 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.

[0093] Embodiment 23

[0094] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.62 P 0.94 Bi 0.0 6S 4.41 O 0.09 Cl 1.5 The raw materials are 2.06 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Bi2O3.

[0095] Embodiment 24

[0096] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 The raw materials are 2.1 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Bi2O3.

[0097] Embodiment 25

[0098] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 Bi 0.0 2S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.02 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of lithium iodide, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.

[0099] Embodiment 26

[0100] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.53 P 0.99 Mg 0.0 1S 4.49 O 0.01 Cl 1.5The raw materials are 2.015 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.01 mol of MgO.

[0101] Embodiment 27

[0102] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.56 P 0.98 Mg 0.0 2S 4.48 O 0.02 Cl 1.5 The raw materials are 2.03 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.02 mol of MgO.

[0103] Embodiment 28

[0104] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.68 P 0.94 Mg 0.0 6S 4.44 O 0.06 Cl 1.5 The raw materials are 2.09 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.06 mol of MgO.

[0105] Embodiment 29

[0106] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 The raw materials are 2.15 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.1 mol of MgO.

[0107] Embodiment 30

[0108] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.56 P 0.98 Mg 0.0 2S 4.48 O 0.02 Cl 1.3 Br 0.1 I 0.1The raw materials are 2.03 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of lithium iodide, 0.49 mol of P2S5 and 0.02 mol of MgO.

[0109] Comparative Example 1

[0110] The difference between this comparative example and Example 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl and 0.5 mol of P2S5.

[0111] Comparative Example 2

[0112] The difference between this comparative example and Example 1 is that the solid electrolyte only includes a core body.

[0113] Comparative Example 3

[0114] The difference between this comparative example and Example 1 is that the mass ratio of sulfide electrolyte, ammonium bifluoride and I2 is 100:150:150.

[0115] The composition and parameters of the core and shell in the solid electrolyte of each embodiment and comparative example are shown in Table 1. Moreover, in one embodiment of the present invention, for example, the stability of the solid electrolyte to air in each embodiment and comparative example is tested, and the measurement results are shown in Table 1. Specifically, the ionic conductivity of the solid electrolyte is measured before and after exposure to humid air with a dew point temperature of -40° for 24 hours, and then the retention rate of the ionic conductivity after exposure for 24 hours is calculated.

[0116] Table 1. Parameters of solid electrolytes in Examples 1 to 30 and Comparative Examples 1 to 3

[0117]

[0118]

[0119] In the present invention, performance tests were performed on all-solid-state batteries prepared using different solid electrolyte membranes in Examples 1 to 30 and Comparative Examples 1 to 3.

[0120] See also Figure 1As shown, in one embodiment of the present invention, for example, the all-solid-state battery in Example 3 is subjected to a room temperature cycle performance test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V to obtain the capacity (CC) and coulombic efficiency (CE) at different cycle numbers. Figure 1 It can be seen that with the increase in the number of cycles, the attenuation trend of the battery CC is relatively gentle, and the battery CE does not fluctuate and stabilizes at around 100%, which indicates that the battery has good cycle performance.

[0121] Please refer to Table 2. In one embodiment of the present invention, for example, the all-solid-state batteries in Examples 1 to 30 and Comparative Examples 1 to 3 are subjected to a room temperature cycle stability test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V. The test is terminated when the battery capacity reaches 80% of the first cycle capacity State of Health (SOH), and the number of room temperature cycles of the battery is recorded. The recorded results are shown in Table 2.

[0122] Table 2. Test results of all-solid-state batteries in Examples 1 to 30 and Comparative Examples 1 to 3

[0123]

[0124]

[0125] Please refer to Table 1 and Table 2. Comparative Examples 1-5, Comparative Examples 2 and Comparative Examples 3 show that as the mass of the fluorine-containing compound and the iodine-containing compound increases, the thickness of the shell gradually increases, and the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery gradually increases first, and then gradually decreases, that is, the normal temperature cycle stability of the battery shows a trend of first increasing and then decreasing, thereby indicating that the shell can improve the electrochemical stability of the solid electrolyte and the stability to air, but when the thickness of the shell is too large, it will greatly prevent the transmission of lithium ions, resulting in a serious reduction in the conductivity of the solid electrolyte, thereby affecting the cycle performance of the battery. Therefore, by controlling the thickness of the shell, the stability of the solid electrolyte and the cycle performance of the battery can be taken into account.

[0126] Please refer to Table 1 and Table 2. By comparing Example 3 with Examples 6 to 9, it can be seen that as the mass of the fluorine-containing compound increases, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the normal temperature cycle stability of the battery shows a trend of first increasing and then decreasing, which shows that: as the mass of the fluorine-containing compound increases, the content of lithium fluoride in the shell increases. Since lithium fluoride has good chemical stability and poor conductivity, the stability of the solid electrolyte to air gradually increases, but the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the mass of the fluorine-containing compound, the stability of the solid electrolyte and the cycle performance of the battery can be taken into account.

[0127] As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 3, 10 and 11 that among the combinations of various fluorine-containing compounds and iodine-containing compounds, the solid electrolyte prepared by combining ammonium bifluoride and I2 has the highest ion conductivity retention rate, that is, the solid electrolyte has the best stability to air, and the number of normal temperature cycles of the battery obtained by this combination is the largest, that is, the battery has the best cycle performance. Therefore, by changing the types of fluorine-containing compounds and iodine-containing compounds, the stability of the solid electrolyte and the cycle performance of the battery can be changed.

[0128] Please refer to Table 1 and Table 2. Comparison of Examples 3, 12 to 14 shows that with the increase in the amount of Sb doped in the sulfide electrolyte, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. Comparison of Examples 16 to 19 shows that with the increase in the amount of In doped in the sulfide electrolyte, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 21 to 24 that as the doping amount of the Bi element in the sulfide electrolyte increases, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the M element in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be taken into account.

[0129] As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 26 to 29 that as the doping amount of the Mg element in the sulfide electrolyte increases, the retention rate of the ionic conductivity of the solid electrolyte gradually increases, that is, the stability of the solid electrolyte to air gradually increases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the E element in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be taken into account.

[0130] Refer to Table 1 and Table 2, and compare Examples 3 and 15, Examples 17 and 20, Examples 22 and 25, and Examples 27 and 30. When the doping amount of Sb, In, Bi or Mg in the sulfide electrolyte is the same, if Br and I are doped into the sulfide electrolyte, the retention rate of the ionic conductivity of the solid electrolyte will decrease, that is, the stability of the solid electrolyte to air will decrease, and the number of normal temperature cycles of the battery will also decrease, that is, the cycle performance of the battery will decrease. Therefore, by controlling the number of element types contained in X or Q in the sulfide electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be further improved.

[0131] Please refer to Table 1 and Table 2. By comparing Example 3, Example 17, Example 22, Example 27 and Comparative Example 1, it can be seen that when the sulfide electrolyte is not doped with Sb, Bi, In or Mg elements, the retention rate of the ionic conductivity of the solid electrolyte will be significantly reduced, that is, the stability of the solid electrolyte to air is very poor, and the number of cycles of the battery at room temperature is only 84, and there is almost no cycle performance, which shows that the Sb, Bi, In or Mg elements doped in the sulfide electrolyte can significantly improve the stability of the solid electrolyte to air and the cycle performance of the battery. Therefore, by controlling the type of element M or E in an electrolyte, the stability of the solid electrolyte and the cycle performance of the battery can be improved.

[0132] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state batteries, and the all-solid-state battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state battery, and therefore includes the advantages of the above-mentioned all-solid-state battery, which will not be elaborated here.

[0133] In summary, the present invention proposes a solid electrolyte and its application, by coating the shell layer on the surface of the core body, on the one hand, it can effectively prevent electrons from being transmitted between the core body and the positive and negative electrode materials, avoid the interface reaction between the core body and the positive and negative electrode materials, improve the stability of the solid electrolyte to the positive and negative electrodes, thereby improving the cycle life and stability of the all-solid-state battery, on the other hand, it can prevent the core body from directly contacting with moisture and oxygen in the air, avoid the core body from reacting with moisture and oxygen in the air, improve the stability of the solid electrolyte to the air, thereby further improving the cycle life of the battery. Moreover, the lithium iodide in the shell layer can effectively improve the ion transmission capacity of the solid electrolyte, enhance the electrochemical performance of the solid electrolyte, and improve the wettability between the solid electrolyte and the positive and negative electrode materials, promote the transmission of ions at the interface between the solid electrolyte and the positive and negative electrode materials, and improve the stability of the interface.

[0134] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0135] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A solid electrolyte, characterized in that At least: a core body including a sulfide electrolyte; and The shell layer is coated on the surface of the core body, and the shell layer includes lithium iodide and lithium fluoride.

2. The solid electrolyte according to claim 1, characterized in that The chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from at least one of Cl, Br or I.

3. The solid electrolyte according to claim 2, characterized in that M is selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is 0 <b≤0.1。 4. The solid electrolyte according to claim 1, characterized in that The chemical formula of the sulfide electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.

5. The solid electrolyte according to claim 4, characterized in that E is Mg, Q is Cl, and the value range of g is 0.01≤g≤0.

1.

6. The solid electrolyte according to claim 1, characterized in that In the shell layer, the mass ratio of the lithium iodide to the lithium fluoride is (1-10):

1.

7. The solid electrolyte according to claim 1, characterized in that The thickness of the shell layer is 1 nm to 100 nm.

8. The solid electrolyte according to claim 1, characterized in that After the solid electrolyte is exposed to moist air with a dew point temperature of -40° for 24 hours, the retention rate of ion conductivity is 55%-96%.

9. An all-solid-state battery, characterized in that: At least: Positive electrode; Negative electrode; as well as A solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane comprises the solid electrolyte described in any one of claims 1-8.

10. An electronic device, characterized in that: Including the all-solid-state battery as described in claim 9.

Citation Information

Patent Citations

  • Core-shell sulfide solid electrolyte, preparation method and all-solid-state battery

    CN116072961A

  • Solid electrolyte with core-shell structure, preparation method of solid electrolyte and solid-state battery

    CN117199511A

  • Positive plate of sulfide solid-state battery, sulfide solid-state battery and device

    WO2020220945A1

  • Solid-state battery, preparation method therefor and application thereof

    WO2021184768A1

  • Inorganic solid-state electrolyte layer of lithium battery, composite negative electrode plate for lithium battery and preparation method therefor, and lithium battery

    WO2023174301A1

Cited By

  • Sulfide electrolyte material, solid electrolyte, electrode plate, battery cell or solid-state battery

    CN120581683A

  • A sulfide electrolyte material, a solid-state electrolyte, an electrode sheet, a battery cell, or a solid-state battery

    CN120581683B